RESEARCH ON TEST METHOD OF FUSELAGE PANEL SUBJECTED TO SHEAR LOAD - ZANG WeiFeng; SU ShaoPu; ZHANG HaiYing; DONG DengKe (Jixie qiangdu)
The test method of fuselage panel subjected to shear load is an important technique for aircraft structure strength research. A new shear test method is proposed based on the property of aircraft fuselage panel subjected to shear load. "D"jig and arch angle connectors is designed to simulate the circular structure of fuselage,and the shear stress is applied through the torsional form of single closed box structure,consisting of "D"jig and fuselage panel through hinge. A test panel and a set of fixtures were designed and manufactured,and validation test were conducted. Validation test verifies the validity and engineering feasibility of this method,and the stress distribution of panel in test is uniform as well as in a good agreement with theoretical analysis. In addition,this test method avoids to design a transition section and a loading section with the similar length of aircraft fuselage panel,and saves assembly work and test expenses. The stability test of the fuselage panel on civil aircraft adopts this new method at present.